The risks of internet addiction: Structure and characteristics of perception - G. F. Romashkina; R. R. Khuziakhmetov (Russian State Vocational Pedagogical University, 2020)
Introduction. Nowadays, digital transformation of society is inevitably accompanied by a set of problems and challenges. Under universal transition to an online format, it is important to analyse how parents assess internet risks for their children and themselves.The aim of the present research is to reveal parents' perceptions of main trends and structural features of children internet addiction.Methodology and research methods. The research is based on the results of a mass survey. The survey was conducted in 2019 according to a multi-stage sample (by gender, age, type of settlement) consisted of the adult population of the Tyumen region. The authors carried out a detailed socio-statistical analysis of internet risks for children based on the self-assessments of all respondents (with the identification of socio-demographic groups), risk assessments for children, according to parents. The structure of "Parents" sub-sample on gender and settlement type is proportional to the structure of the main sample. Under the heading "Children", the authors mean minor children of respondents. The risk of internet addiction is included in the structure of 12 internet risks and examined on the basis of 4 components (behavioural, cognitive, social and affective). In the course of analysis, Alpha Cronbach consistency ratings, index method, Spearman's rank correlation coefficients, Pearson's Goodness-of-Fit Test, F-Test for equality of several means, case classification and triangulation method were applied.Results. The internet transformation of society can be considered an accomplished fact, since the vast majority of people of all ages spend hours online daily. Every fourth respondent notes that their children use the internet from three to four hours a day. The ambivalence of parental attitudes toward internet addiction is manifested in high estimates of its risk for children and young people "in general", and in significantly lower estimates for own children, regardless of the amount of time children spend on the internet, whether they have friends outside the network. Parents clearly articulate negative connotations "in general", but at the same time give very low estimates of dangers in behavioural variables.Scientific novelty. New empirical data, classified on the basis of internet behaviour of children and their parents, as well as parental attitude to this behaviour, have been introduced into the research discourse. An important social issue is identified: in spite of parents' declarations about the risks of dysfunctional (to the detriment of personal interaction, outdoor games and other kinds of activities) internet use by children, the consensus on the features and dangers of internet addiction in society has not been reached yet.Practical significance. The weak articulation and ambivalence of internet addiction problem perception in Russian society is being proved. Insufficient parental awareness of potential internet addiction dangers for children is demonstrated.